Drug-induced liver injury severity and toxicity (DILIst): binary classification of 1279 drugs by human hepatotoxicity. Issue 1 (January 2020) - Thakkar, Shraddha; Li, Ting; Liu, Zhichao; Wu, Leihong; Roberts, Ruth; Tong, Weida
Graphical abstract: Highlights: This drug list provides access to the largest number of drugs classified for human hepatotoxicity. DILIst (DILI severity and toxicity) is the result of augmentation of five DILI related large literature datasets (N > 350 drugs) using a statistical approach. It contains the information for 1279 drugs of which 768 were DILI positives and 511 were DILI negatives. Abstract : Drug-induced liver injury (DILI) is of significant concern to drug development and regulatory review because of the limited success with existing preclinical models. For developing alternative methods, a large drug list is needed with known DILI severity and toxicity. We augmented the DILIrank data set [annotated using US Food and Drug Administration (FDA) drug labeling)] with four literature datasets ( N >350 drugs) to generate the largest drug list with DILI classification, called DILIst (DILI severity and toxicity). DILIst comprises 1279 drugs, of which 768 were DILI positives (increase of 65% from DILIrank), whereas 511 were DILI negatives (increase of 65%). The investigation of DILI positive–negative distribution across various therapeutic categories revealed the most and least frequent DILI categories. Thus, we consider DILIst to be an invaluable resource for the community to improve DILI research.